The Controllability of Monetary Aggregates in Pakistan (The Pakistan Development Review, 1995)
The introduction of new financial i'nstruments l and the consequent asset substitutability since the advent of financial deregulation in 1991 has been accompanied by volatility of the money multiplier and the monetary aggregates. While money demand studies exist [Khan (1980)], the modelIing of the supply side of money and, in general, the impact of financial innovations on money multipliers and monetary aggregates has been largely ignored.2 In a recent study, Siddiqui and Waheed (I994a) found that during 1992-93 the narrow money multiplier felI and increased sharply, causing instability in MI. It was also observed that the broad money multiplier showed similar instability during the same period.